Investigating Primary School Learners’ Knowledge and Awareness of Wild Animals and Their Habitat Before Visiting the Zoological Garden: A Case Study - Photo, Patricia (Jurnal Pendidikan Indonesia Gemilang, 2023)
This research paper examined primary school learners’ knowledge and awareness of wild animals and their habitats before visiting the zoological garden. The study poses two research questions: 1) To what extent do primary school learners demonstrate knowledge and comprehension of wild animals prior to visiting the zoological garden? 2) What is the level of learners' awareness about wild animals’ habitats before visiting the zoological garden? Using a phenomenological approach, the study explored the learners' knowledge and awareness of wild animals. Data was collected through qualitative methods, including drawings, from a sample of six learners aged 10-12 years old. The findings indicate that learners have limited knowledge and comprehension of wild animals and their habitats before visiting the zoological garden. The results also highlight the significance of teachers incorporating information about wild animals’ behaviour and adaptation to their environment when teaching science. The study recommends that zoological gardens offer learners valuable educational opportunities to improve their understanding of these animals.